THE USE OF READING STORYBOOK ON CHILDREN’S VOCABULARY MASTERY - Frederica Mei; Dameria Magdalena Sidabalok; Clarisa Livia Widiaputri; Ahmad Cucus (Universitas Bandar Lampung, 2020)
This article research is about to see the use of English storybook, to describe how storybook is being read in the learning process. The method used is classroom activity especially in student’s responses. The data collected through observation and interview. The observation is about the learning process between teacher and students in the use of reading storybook on children’s vocabulary mastery and the interview is about the teacher’s point of view about the use of reading storybook on children’s vocabulary mastery. The research used descriptive analysis. The process to analyze the data is by observing the student and teacher learning process in the class when the teacher reading storybook through learning process recording done. There are five aspects used to know the student’s responses in the classroom; academic aspects, aspects of thoughts, skill aspects, attitude aspects, and works of habit. The research findings show that children’s storybook can increase children’s vocabulary mastery.